Exploiting the hydrophobic channel of the NNIBP: Discovery of novel diarylpyrimidines as HIV-1 NNRTIs against wild-type and K103N mutant viruses. (15th July 2021) - Fu, Zhipeng; Zhang, Tao; Zhou, Zhongxia; Kang, Dongwei; Sun, Lin; Gao, Shenghua; Cherukupalli, Srinivasulu; De Clercq, Erik; Pannecouque, Christophe; Liu, Xinyong; Zhan, Peng
Graphical abstract: By exploiting the uncharted chemical space around "hydrophobic channel" of the NNIBP, a series of novel DAPYs derivatives with benzyl acyl or sulfonyl-substituted methylenepiperidine were rationally designed, synthesized and evaluated for their inhibitory activity against HIV-1 in MT-4 cells. Among them, FS2 was identified as the most significant compound, which exhibited excellent activity against the HIV-1 wild-type and K103N mutant strains, which are superior to nevirapine and lamivudine. Abstract: To further explore the chemical space surrounding the "hydrophobic channel" of the NNRTI binding pocket (NNIBP), a new series of diarylpyrimidines (DAPYs) were designed and synthesized as potent HIV-1 non-nucleoside RT inhibitors (NNRTIs). The target compounds were evaluated for anti-HIV potency in MT-4 cells. Most of the synthesized DAPYs exhibited moderate to excellent activity against the HIV-1 wild-type (WT) strain with EC50 values ranging from 16 nM to 0.722 µM. Interestingly, few compounds displayed remarkable activity in inhibiting K103N mutant virus with EC50 values ranging from 39 nM to 1.708 µM. Notably, FS2 (EC50(IIIB) = 16 nM, EC50(K103N) = 39 nM, SI = 294) was identified as the most significant compound, which was considerably more potent than nevirapine, lamivudine, and comparable to zidovudine. Additionally, the HIV-1 RT inhibition assay confirmed their binding target. Preliminary structure–activity relationships (SARs) and molecular modeling studies were also performed, providing significant suggestions for further optimization.